Estimation of timber volume and carbon sequestration potential of second generation acacia mangium and acacia hybrid plantations - Nur Syazni, Adam (2015)
The existing Acacia mangium plantations will increasingly play an important role not only for wood production but also in storing and sequestering atmospheric carbon. There are allometric equations estimating biomass and carbon stocks for Acacia mangium, however they were obtained from small trials or experimental plots and very few have been developed for plantations in Sarawak. The purpose of this study was to quantify the aboveground biomass as well as carbon stored and sequestered by two planting variants namely second generation Acacia mangium and Acacia hybrid aged approximately 10 years old. This study also determined the growth rate and yield of these variants. A total of 35 second generation Acacia mangium and 36 Acacia hybrid trees were harvested from a plantation owned by Daiken Sarawak Sdn. Bhd. Fresh weight of leaves, twigs, branches and stems were weighed in the field immediately after tree felling to obtain their green weight. Samples of leaves, twigs, branches and disks were acquired, weighed and packed in a container for laboratory analyses. Growth performance was determined based on five plots of 30 x 30 m established at random in 10-year-old stands of both variants.